Music And Philosophy In Relation To Christian Belief - Octa Maria Sihombing; Jordi Istandar; Evi Mariani (Pusat Riset dan Inovasi Nasional, 2024)
This research explores the relationship between music and philosophy within the context of Christian faith. The research methodology employed is descriptive and qualitative, utilizing a hermeneutic approach that involves literature review, in-depth interviews, and qualitative analysis. The findings indicate that music, as an art form that utilizes sound, plays a significant role in expressing Christian faith, facilitating church worship, and fostering fellowship. Christian philosophy is the study of the nature of reality. It helps to understand the meaning of music in the context of Christian beliefs, examine aspects of music, and develop Christian theology. The Bible provides guidance on the role of music and philosophy in the Christian faith. Music and philosophy complement each other, enriching the religious experience of Christians and encouraging a deeper appreciation of both